Family Quality of Life and its Association with self-efficacy in a Sample of High School Gifted Female Students in Jeddah - Albariqi, Maram Abdullah; Aldhobaiban, Nawal Abdullah (Journal of Educational and Psychological Sciences, 2022)
The study aimed to explore the relationship between the family quality of life and self-efficacy among gifted secondary school female students in Jeddah, in addition to knowing the level of both the family quality of life and self-efficacy for them. The study was of descriptive correlational design, and the sample included (100) of gifted secondary school female students in Jeddah.The researcher used the scale of the family quality of life prepared by AbdulWahhab and Shend (2016), and the scale of self-efficacy prepared by AbdulWahhab and Shend (2015). The study found a statistically significant relationship between family quality of life and self-efficacy among gifted secondary school female students, who had also high level of family quality of life, as well as a high level of self-efficacy.The study recommended instructing the families of the gifted students about their role in raising the self-efficacy of their children, and the importance of cooperation between the family and the school in enhancing self-efficacy and educating students on how to exploit it in daily life and plan for the future.
Keywords: Family quality of life; Self-efficacy; Gifted students